Evaluation of Groundwater Quality for Suitability of Irrigation Purposes: A Case Study in the Udham Singh Nagar, Uttarakhand - Kshitindra Kr. Singh; Geeta Tewari; Suresh Kumar (Journal of Chemistry)
In the present study, the groundwater quality for suitability in agriculture from Udham Singh Nagar district, Uttarakhand, has been evaluated. A total of 50 groundwater samples have been collected and analysed for pH, EC, TH, HCO3−, CO32−, Cl−, SO42−, NO3–, Ca2+, Mg2+, Na+ and K+. To assess the groundwater quality for irrigation purpose, parameters like sodium adsorption ratio (SAR), soluble sodium percentage (SSP), residual sodium carbonate (RSC), magnesium hazards (MHs), permeability index (PI), and chloroalkaline index (CAI) values have been calculated. In USSL diagram, most of the groundwater samples fall in the C2S1 category and were safe for irrigation purpose. Only seven groundwater samples fall in the C3S1 category, indicating medium to high salinity which is safe for irrigation purpose for all types of soils but with limited care of exchangeable sodium. On the basis of RSC, all groundwater samples were observed to be suitable for irrigation purpose. Piper diagram indicated that 50% of the groundwater samples belonged to the Mg2+-Ca2+-HCO3− type and 48% was classified as the Ca2+-Mg2+-Cl− type. Durov diagram suggested possibilities of ion mixing and simple dissolution of ions from polluted soil.